GROSS MORPHOMETRICAL STUDY ON BURSA OF FABRICIUS IN DEVELOPING BRONZE TURKEY (MELEAGRIS GALOPAVO) - G. Penchev (Trakia Journal of Sciences)
The aim of the study was an evaluation of the age related development of bronze turkey's bursa of Fabricius. The obtained data gave information about the standard actual values of the metric parameters in the investigated organ. The bursa of sixty healthy clinically bronze turkeys (30 males and 30 females) was studied metrically by ruler, graph paper and automatic balance. The birds were distributed in 10 age related groups at the 1, 7, 14, 28, 35, 49, 56, 90, 120 and 240 days. Each group consisted of 6 turkeys. The absolute and relative weight, length, perimeter and diameter of the organ were determined. During the period the absolute weight of the bronze turkeys' bursa increased by 76.5 times, the absolute length – 3.5 times. The relative weight of the organ was with the highest values at the 14 days of age. The relative length reached peak values at the 1 day. The relative perimeter was highest at 7 days. The obtained results gave a motivation to make the conclusion that the development of the bronze turkey bursa of Fabricius weight and length were highest from hatching to the sexual maturity.